Validity and reliability of an adapted arabic version of the long international physical activity questionnaire - Khalil Helou; Nour El Helou; Maya Mahfouz; Yara Mahfouz; Pascale Salameh; Mireille Harmouche-Karaki (BMC, 2017)
Abstract Background The International Physical Actvity Questionnaire (IPAQ) is a validated tool for physical activity assessment used in many countries however no Arabic version of the long-form of this questionnaire exists to this date. Hence, the aim of this study was to cross-culturally adapt and validate an Arabic version of the long International Physical Activity Questionnaire (AIPAQ) equivalent to the French version (F-IPAQ) in a Lebanese population. Methods The guidelines for cross-cultural adaptation provided by the World Health Organization and the International Physical Activity Questionnaire committee were followed. One hundred fifty-nine students and staff members from Saint Joseph University of Beirut were randomly recruited to participate in the study. Items of the A-IPAQ were compared to those from the F-IPAQ for concurrent validity using Spearman's correlation coefficient. Content validity of the questionnaire was assessed using factor analysis for the A-IPAQ's items. The physical activity indicators derived from the A-IPAQ were compared with the body mass index (BMI) of the participants for construct validity. The instrument was also evaluated for internal consistency reliability using Cronbach's alpha and Intraclass Correlation Coefficient (ICC). Finally, thirty-one participants were asked to complete the A-IPAQ on two occasions three weeks apart to examine its test-retest reliability. Bland-Altman analyses were performed to evaluate the extent of agreement between the two versions of the questionnaire and its repeated administrations. Results A high correlation was observed between answers of the F-IPAQ and those of the A-IPAQ, with Spearman's correlation coefficients ranging from 0.91 to 1.00 (p < 0.05). Bland-Altman analysis showed a high level of agreement between the two versions with all values scattered around the mean for total physical activity (mean difference = 5.3 min/week, 95% limits of agreement = −145.2 to 155.8). Negative correlations were observed between MET values and BMI, independent of age, gender or university campus. The A-IPAQ showed a high internal consistency reliability with Cronbach's alpha ranging from 0.769-1.00 (p < 0.001) and intraclass correlation coefficient (ICC) ranging from 0.625-0.999 (p < 0.001), except for a moderate agreement with the moderate garden/yard activity (alpha = 0.682; ICC = 0.518; p < 0.001). The A-IPAQ had moderate-to-good test-retest reliability for most of its items (ICC ranging from 0.66-0.96; p < 0.001) and the Bland-Altman analysis showed a satisfactory agreement between the two administrations of the A-IPAQ for total physical activity (mean difference = 99.8 min/week, 95% limits of agreement = −1105.3; 1304.9) and total vigorous and moderate physical activity (mean difference = −29.7 min/week, 95% limits of agreement = −777.6; 718.2). Conclusion The modified Arabic version of the IPAQ showed acceptable validity and reliability for the assessment of physical activity among Lebanese adults. More studies are necessary in the future to assess its validity compared to a gold-standard criterion measure.